Frezhub: From farm to fork - Noor Fzlinda Fabeil; Khairul Hanim Pazim@Fadzim; Juliana Langgat; Norhayati Daut (Readers Insight Publisher, 2021)
This study reveals in order to avoid the dumping of farm produce and loss of regular market during the pandemic crisis, smallholder farmers demonstrate alternative distribution strategies to sustain their business, including distributing their produce through the local runner and marketing via social media. This alternative supply chain embraces the concept of the hub chain model, which provide insight into the conceptualisation of an integrated chain called FrezHub. The novelty of FrezHub is the use of ‘hub agent’ in the chain to replace multiple intermediaries and serve as ‘just-in-time hub’ between farmers and customers.